Silicon-carbon composite material and preparation method thereof, negative electrode sheet, secondary battery and electrical device

By depositing a silicon-based material layer of sub-nano silicon and sub-nano silicon carbide clusters in the pores of the porous carbon matrix, the problems of high expansion and short cycle life of silicon-carbon composite materials during charging and discharging are solved, and low expansion and long The cycle life improves the stability and energy density of the electrode.

CN117174882BActive Publication Date: 2025-02-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311444808.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-02
Publication Date
2025-02-14
Estimated Expiration
2043-11-02

AI Technical Summary

Technical Problem

Existing silicon-carbon composite materials have problems of high expansion and short cycle life during charging and discharging, resulting in rapid attenuation of electrode capacity.

Method used

By depositing a silicon-based material layer of sub-nano silicon clusters and sub-nano silicon carbide clusters in the pores of the porous carbon matrix, the size growth of silicon is limited, forming sub-nano silicon carbide clusters and sub-nano silicon clusters in surface contact with each other. , reduce the expansion stress of the material.

Benefits of technology

Low expansion and long cycle life are achieved, improving the stability and energy density of the electrodes, while improving fast charging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117174882B_ABST
    Figure CN117174882B_ABST
Patent Text Reader

Abstract

The present application relates to a silicon-carbon composite material and a preparation method thereof, a negative electrode plate, a secondary battery and an electrical device. The silicon-carbon composite material includes a porous carbon matrix and a silicon-based material layer located in the pores of the porous carbon matrix, and the silicon-based material layer includes sub-nano silicon clusters and sub-nano silicon carbide clusters, and the surface of the sub-nano silicon carbide clusters is in contact with the surface of the sub-nano silicon clusters. The silicon-carbon composite material has low expansion, good cycle performance and fast charging performance, and can also have a higher energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.

[0003] Silicon-based materials have attracted attention because of their much higher capacity than carbon-based materials, because higher capacity means higher energy density can be achieved. However, silicon-based materials will produce huge volume changes (>300%) during the charging and discharging process. This change will cause material structure damage and particle pulverization, which will lead to rapid attenuation of electrode capacity and even electrode failure. Therefore, silicon-based materials and carbon-based materials are often used in combination when making pole pieces. However, the current silicon-carbon composite materials still have problems with high expansion and short cycle life. Summary of the invention

[0004] The present application provides a silicon-carbon composite material with low expansion and long cycle life and a preparation method thereof, as well as a negative electrode sheet, a secondary battery and an electrical device using the silicon-carbon composite material.

[0005] In a first aspect of the present application, a silicon-carbon composite material is provided, comprising a porous carbon matrix and a silicon-based material layer located in the pores of the porous carbon matrix, wherein the silicon-based material layer comprises sub-nano silicon clusters and sub-nano silicon carbide clusters, and the surfaces of the sub-nano silicon carbide clusters are in contact with the surfaces of the sub-nano silicon clusters.

[0006] The silicon-carbon composite material is provided with a silicon-based material layer in the pores of a porous carbon matrix, and the pores can reserve space for the expansion of silicon, thereby reducing the breakage of silicon-carbon composite material particles and improving the cycle life. At the same time, the presence of silicon carbide limits the size growth of silicon, promotes the formation of sub-nanometer silicon clusters, and finally forms sub-nanometer silicon carbide clusters and the sub-nanometer silicon clusters in contact with each other on the surface. Compared with traditional nano-silicon, the sub-nanometer silicon clusters have smaller expansion, reduce the expansion stress of the material, further reduce the breakage of silicon-carbon composite material particles, and improve the cycle performance.

[0007] In one embodiment, the radial size of the sub-nanometer silicon cluster is 0.2nm~1nm.

[0008] In one embodiment, the radial size of the sub-nanometer silicon carbide clusters is 0.2 nm to 1 nm.

[0009] In one embodiment, the specific surface area of ​​the porous carbon matrix is ​​≥800m 2 / g. By using a porous carbon matrix with ultra-high specific surface area, more silicon-based materials can be deposited, thereby improving the high energy density of the material.

[0010] Optionally, the specific surface area of ​​the porous carbon matrix is ​​800 m 2 / g~2000m 2 / g.

[0011] Further optionally, the specific surface area of ​​the porous carbon matrix is ​​800m 2 / g~1700m 2 / g.

[0012] Further optionally, the specific surface area of ​​the porous carbon matrix is ​​800m 2 / g~1200m 2 / g.

[0013] In one embodiment, the total volume of the silicon-based material layer is less than the total volume of the pores.

[0014] Optionally, the total volume of the silicon-based material layer accounts for 10% to 60% of the total volume of the pores. This can improve the high energy density on the one hand, reduce the breakage of silicon-carbon composite material particles on the other hand, improve the cycle performance, and also optimize the fast charging performance to a certain extent.

[0015] Further optionally, the total volume of the silicon-based material layer accounts for 10% to 50% of the total volume of the pores.

[0016] Further optionally, the total volume of the silicon-based material layer accounts for 10% to 30% of the total volume of the pores.

[0017] In one embodiment, the thickness of the silicon-based material layer is less than the pore diameter of the pore.

[0018] Optionally, the average pore size of the pores is 5 nm to 50 nm. This can improve the high energy density on the one hand, reduce the breakage of silicon-carbon composite material particles on the other hand, improve the cycle performance, and also improve the fast charging performance to a certain extent.

[0019] Further optionally, the average pore diameter of the pores is 5 nm to 40 nm.

[0020] Further optionally, the average pore diameter of the pores is 5 nm to 25 nm.

[0021] Optionally, the average thickness of the silicon-based material layer is 2 nm to 20 nm.

[0022] Further optionally, the average thickness of the silicon-based material layer is 2 nm to 18 nm.

[0023] Further optionally, the average thickness of the silicon-based material layer is 2 nm to 10 nm.

[0024] In one embodiment, the particle size Dv50 of the silicon-carbon composite material is 3 μm to 30 μm. This can reduce the deterioration of cycle performance caused by side reactions during the cycle, reduce the diffusion distance of ions, improve fast charging performance, and have a better cycle life.

[0025] Optionally, the particle size Dv50 of the silicon-carbon composite material is 10 μm to 30 μm.

[0026] Further optionally, the particle size Dv50 of the silicon-carbon composite material is 10 μm to 20 μm.

[0027] In one of the embodiments, the surface of the porous carbon matrix is ​​further coated with a coating layer.

[0028] Optionally, the coating layer includes a carbon coating layer; further optionally, the material of the carbon coating layer includes amorphous carbon; optionally, the average thickness of the coating layer is 5nm~60nm.

[0029] In one embodiment, in the silicon-carbon composite material, the mass percentage of silicon element is 20% to 40%, and the mass percentage of carbon element is 60% to 80%.

[0030] In one embodiment, the silicon-carbon composite material includes one or both of the following features:

[0031] (1) Tap density is 0.7g / cm 3 ~1.3g / cm 3 ;

[0032] (2) Specific surface area is 0.8m 2 / g ~1.5m 2 / g.

[0033] In a second aspect of the present application, a method for preparing a silicon-carbon composite material is provided, comprising the following steps:

[0034] A silicon-based material layer is deposited in the pores of the porous carbon matrix, wherein the silicon-based material layer includes sub-nanometer silicon clusters and silicon carbide clusters, and the surface of the silicon carbide clusters is in contact with the surface of the sub-nanometer silicon clusters.

[0035] The preparation method has simple steps and is suitable for industrial promotion and application.

[0036] In one embodiment, depositing a silicon-based material layer in the pores of a porous carbon matrix comprises:

[0037] The porous carbon substrate is placed in a reaction container, and a mixed gas of a silicon source gas and a carbon source gas is introduced to perform vapor deposition.

[0038] In one embodiment, the introduction of a mixed gas of silicon source gas and carbon source gas for vapor deposition includes one or more of the following features:

[0039] (1) In the mixed gas, the volume ratio of the silicon source gas to the carbon source gas is 10:(1-5);

[0040] (2) The silicon source gas includes SiH4;

[0041] (3) The carbon source gas includes C2H4;

[0042] (4) The flow rate of the mixed gas is 0.05L / min~0.2L / min;

[0043] (5) The deposition temperature is 400℃~600℃;

[0044] (6) The deposition time is 30 minutes to 2 hours.

[0045] In one embodiment, after depositing the silicon-based material layer, the step of preparing a coating layer on the surface of the porous carbon matrix is ​​also included;

[0046] Optionally, the method for preparing the coating layer on the surface of the porous carbon substrate comprises a vapor deposition method.

[0047] In one embodiment, the method for preparing the porous carbon matrix includes a template method, an acid-base activation method or a pyrolysis method; optionally, the method for preparing the porous carbon matrix includes an acid-base activation method.

[0048] In one embodiment, the method for preparing the porous carbon substrate comprises:

[0049] mixing a template, a carbon source and a solvent to prepare a carbon solution;

[0050] The carbon solution is subjected to a first heat treatment and then dried to prepare an expanded carbon precursor;

[0051] subjecting the expanded carbon precursor to a second heat treatment to prepare a carbonized intermediate;

[0052] The template in the carbonized intermediate is removed to prepare the porous carbon matrix.

[0053] In one embodiment, the method for preparing the porous carbon matrix has one or more of the following characteristics:

[0054] (1) The mass ratio of the template to the carbon source is (1-10):1;

[0055] (2) The temperature of the first heat treatment is 70℃~90℃ and the time is 6h~10h;

[0056] (3) The drying temperature is 120℃~140℃ and the drying time is 1h~4h;

[0057] (4) The second heat treatment includes: heating to 400°C~600°C at a heating rate of 3°C / min~10°C / min and maintaining for 2h~6h.

[0058] According to a third aspect of the present application, a negative electrode plate is provided, comprising a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises one or more of the silicon-carbon composite material described in the first aspect and the silicon-carbon composite material prepared by the preparation method described in the second aspect.

[0059] The negative electrode plate of the present application includes the silicon-carbon composite material provided in the present application, and thus has at least the same advantages as the silicon-carbon composite material.

[0060] A fourth aspect of the present application provides a secondary battery comprising the negative electrode sheet described in the third aspect.

[0061] The secondary battery of the present application includes the negative electrode sheet provided by the present application, and thus has at least the same advantages as the negative electrode sheet.

[0062] In a fifth aspect of the present application, there is provided an electrical device comprising one or more of the negative electrode plate described in the third aspect and the secondary battery described in the fourth aspect.

[0063] The electric device of the present application includes the negative electrode sheet or the secondary battery provided in the present application, and thus has at least the same advantages as the negative electrode sheet or the secondary battery.

[0064] Details of one or more embodiments of the present application are set forth in the following drawings and descriptions. Other features, objectives, and advantages of the present application will become apparent from the contents recorded in the specification and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0066] Figure 1 A schematic diagram of a battery cell according to an embodiment of the present application;

[0067] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown;

[0068] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0069] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application;

[0070] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0071] Figure 6 A schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source;

[0072] Figure 7 This is an electron microscope image of a porous carbon substrate according to one embodiment of the present application;

[0073] Figure 8 This is an electron microscope image of a silicon-based material layer according to one embodiment of the present application;

[0074] Fig. 9 This is an electron microscope image of a silicon-carbon composite material according to an embodiment of the present application;

[0075] Description of reference numerals:

[0076] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION

[0077] Below, some embodiments of the silicon-carbon composite material and its preparation method, negative electrode plate, secondary battery and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0078] The "range" disclosed in the present application can be limited in the form of a lower limit and an upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The range limited in this way can be including or excluding end values, and any end value can be included or not included independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0079] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0080] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0081] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0082] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0083] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0084] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0085] Traditional silicon-carbon composite materials are prepared by directly mixing silicon-based materials with carbon-based materials, or coating the surface of silicon-based materials with a layer of carbon-based materials, or granulating silicon-based materials and carbon-based materials. These materials have large restrictions on the silicon content. When the silicon content is too high, the expansion is still large, which makes the electrode structure easily damaged, thereby shortening the cycle life.

[0086] Based on the above problems, some examples of the present application provide a silicon-carbon composite material, which includes a porous carbon matrix and a silicon-based material layer located in the pores of the porous carbon matrix, the silicon-based material layer includes sub-nano silicon clusters and sub-nano silicon carbide clusters, and the surfaces of the sub-nano silicon carbide clusters are in contact with the surfaces of the sub-nano silicon clusters.

[0087] The silicon-carbon composite material is provided with a silicon-based material layer in the pores of a porous carbon matrix, and the pores can reserve space for the expansion of silicon, thereby reducing the breakage of the silicon-carbon composite material particles and improving the cycle life. At the same time, in the silicon-based material layer, the presence of silicon carbide limits the size growth of silicon, promotes the formation of sub-nanometer silicon clusters, and finally forms sub-nanometer silicon carbide clusters and sub-nanometer silicon clusters in contact with each other on the surface. Compared with traditional nano-silicon, the sub-nanometer silicon clusters have smaller expansion, which reduces the expansion stress of the material, further reduces the breakage of the silicon-carbon composite material particles, and improves the cycle performance. The radial size of the sub-nanometer silicon clusters is smaller, which can reduce the diffusion distance of ions, improve solid phase diffusion, and improve fast charging performance.

[0088] In addition, the above silicon-carbon composite material can also take into account the high energy density characteristics of silicon-based materials.

[0089] It can be understood that the silicon-based material can form a layer structure within the pores of the porous carbon matrix by methods such as deposition.

[0090] Furthermore, the radial size of the sub-nanometer silicon cluster is 0.2nm~1nm.

[0091] Furthermore, the radial size of the sub-nanometer silicon carbide cluster is 0.2nm~1nm.

[0092] In some examples, the specific surface area of ​​the porous carbon matrix is ​​≥800 m 2 / g. By using a porous carbon matrix with an ultra-high specific surface area, more silicon-based materials can be deposited, thereby increasing the high energy density of the material. Furthermore, the specific surface area of ​​the porous carbon matrix is ​​800m 2 / g~2000m 2 / g. In this way, the cycle performance can be improved under high energy density. Specifically, the specific surface area of ​​the porous carbon matrix includes but is not limited to: 800m 2 / g、900m 2 / g、1000m2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g or a range between any two of the foregoing. Further, the specific surface area of ​​the porous carbon matrix is ​​800m 2 / g~1700m 2 / g. Furthermore, the specific surface area of ​​the porous carbon matrix is ​​800m 2 / g~1200m 2 Without limitation, the specific surface area of ​​the porous carbon substrate can be measured by a nitrogen isothermal adsorption-desorption method.

[0093] In some examples, the total volume of the silicon-based material layer is less than the total volume of the pores. Further, the total volume of the silicon-based material layer accounts for 10% to 60% of the total volume of the pores. In this way, on the one hand, the content of silicon-based materials is large, and the high energy density is improved. On the other hand, more expansion space is provided for silicon-based materials, the crushing of silicon-carbon composite material particles is reduced, and the cycle performance is improved. In addition, the fast charging performance can be optimized to a certain extent. Specifically, the total volume of the silicon-based material layer accounts for the total volume of the pores, including but not limited to: 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range between any two of the foregoing. Further, the total volume of the silicon-based material layer accounts for 10% to 50% of the total volume of the pores. Further, the total volume of the silicon-based material layer accounts for 10% to 30% of the total volume of the pores. Without limitation, the total volume of the silicon-based material layer can be obtained by calculating the pore volume of the porous carbon matrix before and after the deposition of the silicon-based material layer (which can be determined by nitrogen isothermal adsorption and desorption method).

[0094] In some examples, the thickness of the silicon-based material layer is less than the pore diameter of the pore.

[0095] Furthermore, the average pore size of the pores is 5nm~50nm. In this way, on the one hand, the content of silicon-based materials is larger, and the high energy density is improved. On the other hand, more expansion space is provided for silicon-based materials, the breakage of silicon-carbon composite material particles is reduced, and the cycle performance is improved. In addition, the fast charging performance can be improved to a certain extent. Specifically, the average pore size of the pores includes but is not limited to: 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm or a range between any two of the foregoing. Furthermore, the average pore size of the pores is 5nm~40nm. Still further, the average pore size of the pores is 5nm~25nm. Without limitation, the average pore size of the pores can be determined by a nitrogen isothermal adsorption and desorption method.

[0096] Furthermore, the average thickness of the silicon-based material layer is 2nm~20nm. In this way, on the one hand, the content of silicon-based materials is large, and the high energy density is improved. On the other hand, more expansion space is provided for silicon-based materials, the breakage of silicon-carbon composite material particles is reduced, and the cycle performance is improved. In addition, the fast charging performance can be improved to a certain extent. Specifically, the average thickness of the silicon-based material layer includes but is not limited to: 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm or a range between any two of the foregoing. Furthermore, the average thickness of the silicon-based material layer is 2nm~18nm. Furthermore, the average thickness of the silicon-based material layer is 2nm~10nm. Without limitation, it can be measured by an indirect method. Specifically: the average pore size of the porous carbon matrix before depositing the silicon-based material layer (which can be measured by the nitrogen isothermal adsorption-desorption method) is denoted as R1, and after depositing silicon, the average pore size is denoted as R2, then the average thickness of the silicon-based material layer is (R1-R2) / 2.

[0097] In some examples, the particle size Dv50 of the silicon-carbon composite material is 3μm~30μm. In this way, on the one hand, the deterioration of the cycle performance caused by side reactions during the cycle can be reduced, and on the other hand, the diffusion distance of ions can be reduced, the fast charging performance can be improved, and it also has a good cycle life. Specifically, the particle size Dv50 of the silicon-carbon composite material includes but is not limited to: 3μm, 5μm, 8μm, 10μm, 12μm, 15μm, 20μm, 25μm, 30μm. Further, the particle size Dv50 of the silicon-carbon composite material is 10μm~30μm. Furthermore, without limitation, the particle size Dv50 of the silicon-carbon composite material is 10μm~20μm. The particle size Dv50 of the silicon-carbon composite material can be tested by laser particle size.

[0098] In some of the examples, the surface of the porous carbon substrate is further coated with a coating layer.

[0099] In some examples, the coating layer includes a carbon coating layer. Without limitation, the material of the carbon coating layer includes amorphous carbon.

[0100] In some examples, the average thickness of the coating layer is 5 nm to 60 nm. This can better isolate the corrosion of the electrolyte to the inside of the material during the cycle, and can also improve the conductivity of the material. Without limitation, the average thickness of the carbon coating layer can be tested by transmission electron microscopy or sputtering XPS.

[0101] In some examples, in the silicon-carbon composite material, the mass percentage of silicon is 20% to 40%, and the mass percentage of carbon is 60% to 80%. This allows the material to have both high gram capacity and low expansion. Without limitation, the content of silicon and carbon can be tested by ICP testing.

[0102] In some examples, the tap density of the silicon-carbon composite material is 0.7 g / cm 3 ~1.3g / cm 3 .

[0103] In some examples, the specific surface area of ​​the silicon-carbon composite material is 0.8 m 2 / g ~1.5m 2 / g.

[0104] Some other examples of the present application provide a method for preparing a silicon-carbon composite material, comprising the following steps:

[0105] A silicon-based material layer is deposited in the pores of the porous carbon matrix, wherein the silicon-based material layer includes sub-nanometer silicon clusters and silicon carbide clusters, and the surface of the silicon carbide clusters is in contact with the surface of the sub-nanometer silicon clusters.

[0106] The preparation method has simple steps and is suitable for industrial promotion and application.

[0107] In addition, it can be understood that the silicon-carbon composite material involved in the above preparation method has the same characteristics and advantages as the silicon-carbon composite material in the above examples, which will not be described in detail here.

[0108] Furthermore, sub-nano silicon-based materials can reduce expansion stress, thereby reducing the breakage of material particles, while also reducing ion diffusion distance, improving solid phase diffusion, and improving fast charging performance; combined with a porous carbon matrix to reserve space for silicon-based material expansion, it can greatly reduce expansion. Therefore, a further purpose of this application is to prepare sub-nano silicon-based materials.

[0109] Some examples of depositing a layer of silicon-based material within the pores of a porous carbon matrix include:

[0110] The porous carbon substrate is placed in a reaction container, and a mixed gas of a silicon source gas and a carbon source gas is introduced to perform vapor deposition.

[0111] Furthermore, in the mixed gas, the volume ratio of the silicon source gas to the carbon source gas is 10:(1-5). Specifically, the volume ratio of the silicon source gas to the carbon source gas includes but is not limited to: 10:1, 10:2, 10:3, 10:4, 10:5 or a range between any two of the foregoing.

[0112] Without limitation, the silicon source gas includes SiH 4 .

[0113] Without limitation, the carbon source gas includes C2H4.

[0114] Further, the flow rate of the mixed gas is 0.05L / min~0.2L / min. Specifically, the flow rate of the mixed gas includes but is not limited to: 0.05L / min, 0.08L / min, 0.1L / min, 0.12L / min, 0.15L / min, 0.2L / min or a range between any two of the foregoing.

[0115] Further, the deposition temperature is 400° C. to 600° C. Specifically, the deposition temperature includes but is not limited to: 400° C., 450° C., 500° C., 550° C., 600° C. or a range between any two of the foregoing.

[0116] Furthermore, the deposition time is 30 min to 2 h. Specifically, the deposition time includes but is not limited to: 30 min, 1 h, 1.5 h, 2 h or a range between any two of the foregoing.

[0117] By adopting the vapor deposition method to prepare the silicon-based material layer and rationally regulating the gas ratio, flow rate, temperature and time during the preparation process, the generated silicon carbide can be made to surround the silicon after nucleation, limiting the growth of its size, and finally forming a silicon-based material layer including sub-nanometer silicon clusters and silicon carbide clusters, and the surface of the silicon carbide clusters is in contact with the surface of the sub-nanometer silicon clusters.

[0118] In some of the examples, after depositing the silicon-based material layer, a step of preparing a coating layer on the surface of the porous carbon substrate is also included. Furthermore, the method for preparing the coating layer on the surface of the porous carbon substrate includes a vapor deposition method. Without limitation, the coating layer is a carbon coating layer, the carbon source gas used can be one or both of CH4 and C2H2, the deposition temperature can be 600°C~900°C, and the time can be controlled according to the preset thickness, for example, 15min~30min.

[0119] In some of the examples, the preparation method of the porous carbon matrix includes a template method, an acid-base activation method or a thermal decomposition method.

[0120] As an example, the template method can use SiO2 nanospheres as templates, immerse them in a carbon source solution, and obtain the porous carbon matrix through centrifugation, drying, annealing, and acid etching.

[0121] As an example, the acid-base activation method can mix activators such as potassium hydroxide and phosphoric acid with a carbon source, and remove organic matter and natural templates inside the carbon source through physical and chemical spark action to obtain the porous carbon matrix. Potassium hydroxide as a chemical activator can generate potassium carbonate, potassium oxide, and even metallic potassium, which are then removed in subsequent pyrolysis and washing, while phosphoric acid can generate phosphorus-containing functional groups in the carbon matrix to promote the formation of micropores.

[0122] As an example, the pyrolysis method refers to obtaining the porous carbon matrix by pyrolysis by relying on the gas generated by pyrolysis and the characteristics of the material itself without adding any template or activator.

[0123] Furthermore, the preparation method of the porous carbon matrix includes an acid-base activation method.

[0124] In some examples, the method for preparing the porous carbon substrate includes:

[0125] mixing a template, a carbon source and a solvent to prepare a carbon solution;

[0126] The carbon solution is subjected to a first heat treatment and then dried to prepare an expanded carbon precursor;

[0127] subjecting the expanded carbon precursor to a second heat treatment to prepare a carbonized intermediate;

[0128] The template in the carbonized intermediate is removed to prepare the porous carbon matrix.

[0129] Further, the mass ratio of the template to the carbon source is (1-10): 1. Specifically, the mass ratio of the template to the carbon source includes but is not limited to: 1: 1, 2: 1, 2.7: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1 or a range between any two of the foregoing.

[0130] Furthermore, the temperature of the first heat treatment is 70°C to 90°C and the time is 6h to 10h. Specifically, the temperature of the first heat treatment includes but is not limited to: 70°C, 75°C, 80°C, 85°C, 90°C or a range between any two of the foregoing. The time of the first heat treatment includes but is not limited to: 6h, 7h, 8h, 9h, 10h or a range between any two of the foregoing.

[0131] Furthermore, the drying temperature is 120° C. to 140° C., and the drying time is 1 h to 4 h.

[0132] Further, the second heat treatment includes: heating to 400°C~600°C at a heating rate of 3°C / min~10°C / min, and maintaining for 2h~6h. Specifically, the heating rate of the second heat treatment includes but is not limited to: 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or a range between any two of the foregoing. The temperature of the second heat treatment includes but is not limited to: 400°C, 450°C, 500°C, 550°C, 600°C or a range between any two of the foregoing. The time of the second heat treatment includes but is not limited to: 2h, 3h, 4h, 5h, 6h or a range between any two of the foregoing.

[0133] In addition, without limitation, the method of removing the template in the carbonized intermediate may include acid treatment, for example, mixing the carbonized intermediate with an acid solution and performing a third heat treatment, followed by washing and drying.

[0134] Some other examples of the present application provide a negative electrode plate, including a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, the negative electrode active material layer including one or more of the silicon-carbon composite material as described above and the silicon-carbon composite material prepared by the preparation method as described above.

[0135] Some other examples of the present application provide a secondary battery, comprising the negative electrode sheet as described above.

[0136] Some other examples of the present application provide an electrical device, comprising one or more of the negative electrode plate described above and the secondary battery described above.

[0137] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0138] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0139] Positive electrode

[0140] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode plate is different when the battery is discharged to different states. In the list of positive electrode materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode materials is also within the scope of the positive electrode material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode material, and non-limiting examples include coating modification.

[0141] In the list of positive electrode materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.

[0142] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.

[0143] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0144] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0145] In some of the embodiments, the positive electrode active material may be a positive electrode active material for a battery known in the art. As a non-limiting example, the positive electrode active material may include one or more of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Non-limiting examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.85 Co 0.15 Al 0.05 O2.

[0146] In some embodiments, the positive electrode active material layer may further include a binder. As non-limiting examples, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0147] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0148] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000~25000mPa·s. When coating the cathode slurry, the coating unit surface density based on dry weight (excluding solvent) can be 15~35 mg / cm 2 The compaction density of the positive electrode can be 3.0~3.6 g / cm 3 , can be selected as 3.3~3.5 g / cm 3 .

[0149] Negative electrode

[0150] The negative electrode plate is as described above.

[0151] In addition, as a non-limiting example, the negative electrode current collector has two surfaces facing each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two facing surfaces of the negative electrode current collector.

[0152] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0153] In some of the embodiments, the above-mentioned silicon-carbon composite material can be used alone in the negative electrode active material layer, or the silicon-carbon composite material can be mixed with other negative electrode active materials for batteries known in the art in any proportion. As a non-limiting example, other negative electrode active materials for batteries may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0154] In some embodiments, the carbon-based material includes one or more of artificial graphite, natural graphite, soft carbon and hard carbon.

[0155] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0156] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0157] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0158] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000~10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75~220 g / m 2 The compaction density of the negative electrode sheet can be 1.0 g / cm 3 ~ 1.8 g / cm 3 .

[0159] Electrolytes

[0160] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0161] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0162] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0163] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, )、ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate ( ), fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0164] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0165] In some embodiments, the additive in the electrolyte may include, but is not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.

[0166] Isolation film

[0167] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0168] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0169] In some embodiments, the isolation film has a thickness of 6 to 40 μm, and may be 12 to 20 μm.

[0170] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0171] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0172] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0173] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.

[0174] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.

[0175] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0176] In some of these embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.

[0177] The secondary battery may be a battery module 4 or a battery pack 1 .

[0178] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.

[0179] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0180] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0181] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0182] Figure 4 and Figure 51 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0183] In addition, the present application also provides an electrical device, which includes a secondary battery provided by the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.

[0184] As an electrical device, a secondary battery can be selected according to its usage requirements.

[0185] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0186] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source. Example

[0187] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0188] Example 1

[0189] 1) Preparation of positive electrode

[0190] The positive electrode active material NCM811, the conductive carbon black SP and the binder PVDF were dispersed in the solvent NMP in a weight ratio of 98:1:1 and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the double-sided surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained, wherein the coating amount per unit area of ​​both sides was 0.27g / 1540.25mm 2 .

[0191] 2) Preparation of negative electrode sheet

[0192] 2.1 Preparation of negative electrode active materials

[0193] Preparation of porous carbon matrix: Take 11g of glucose monohydrate and 30g of zinc chloride and place them in a 200mL beaker, add 30mL of deionized water, and stir with a glass rod to form a clear and transparent solution. Transfer the solution to a constant temperature heated magnetic stirrer, heat it to 80℃, and slowly stir it mechanically with a stirring paddle for 8h to evaporate most of the water. The residue forms a uniform brown-black viscous liquid. Preheat the air drying oven to 130℃, and immediately put the brown-black viscous liquid into it while it is hot, keep it for 2h, and obtain a loose and porous expanded carbon precursor. After the carbon precursor is cooled to room temperature, it is loaded with a magnetic boat and sent to a tubular resistance furnace. The heating rate is controlled to 6℃ / min, and the temperature is raised to 500℃ and maintained for 4h. N2 protection is introduced throughout the carbonization process.

[0194] Prepare 250mL of 1mol / L dilute hydrochloric acid, grind the carbonized product cooled to room temperature into powder with an agate mortar, take 50mL of 1mol / L dilute hydrochloric acid and mix all the powder in a conical flask, heat to boiling on a constant temperature heating magnetic stirrer and keep it for 20 minutes, repeat 4 times to wash away the template in the carbon material. After filtering out the washing liquid, wash the carbon material with a large amount of deionized water until it is neutral and put it in a forced air drying oven at 110°C for 20 hours to prepare a porous carbon matrix. The electron microscope image of the porous carbon matrix is ​​as follows Figure 7 As shown, it can be seen that the prepared carbon matrix has a porous structure.

[0195] Preparation of silicon-based material layer: The porous carbon matrix is ​​placed in a tube furnace, and a mixed gas of SiH4 and C2H4 (volume ratio is between 10:3) is introduced at a temperature of 500°C and a ventilation rate of 0.1L / min for 1 hour to deposit the silicon-based material layer in the pores of the porous carbon matrix. The electron microscope image of the silicon-based material layer is shown in FIG. Figure 8 As shown, it can be seen that the silicon-based material layer includes sub-nanometer silicon clusters and silicon carbide clusters, and the surfaces of the two are in contact, or the silicon carbide clusters are located around the sub-nanometer silicon clusters, the radial size of the sub-nanometer silicon clusters is about 0.2nm~1nm, and the radial size of the sub-nanometer silicon carbide clusters is about 0.2nm~1nm.

[0196] Preparation of carbon coating: The gas introduced was then replaced with CH4, the temperature was set to 700°C, and the temperature was maintained for 25 minutes to form an amorphous carbon coating on the surface of the porous carbon matrix. The amorphous carbon coating was then cooled to room temperature to obtain a silicon-carbon composite material. The thickness of the amorphous carbon coating was 30 nm. The electron microscope image of the silicon-carbon composite material is shown below: Fig. 9 shown.

[0197] 2.2. The silicon-carbon composite material prepared in step 2.1 is used as the negative electrode active material, mixed with a thickener of sodium carboxymethyl cellulose, a binder of styrene-butadiene rubber, and a conductive agent of acetylene black in a mass ratio of 97:1:1:1, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on both sides of the copper foil; the copper foil is dried at room temperature and then transferred to a 120°C oven for drying for 1 hour, and then super-cold pressed and cut to obtain a negative electrode sheet, wherein the coating amount per unit area on both sides is 0.17 g / 1540.25 mm 2 .

[0198] 3) Isolation film

[0199] A 12μm thick polypropylene isolation film was selected.

[0200] 4) Preparation of electrolyte

[0201] The organic solvent is a mixed solution containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, EMC and DEC is 20:20:60. In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt LiPF6 is dissolved in the organic solvent and mixed evenly to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L.

[0202] 5) Preparation of batteries

[0203] The positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role. Then, they are wound into a square bare battery cell, loaded with aluminum-plastic film, and then baked at 80°C to remove water. After that, 10g of the corresponding non-aqueous electrolyte is injected and sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a finished battery with a capacity of 4000mAh is obtained.

[0204] The secondary batteries of Examples 2 to 18 are prepared in a similar manner to that of Example 1, with the main differences being the specific surface area of ​​the porous carbon matrix, the total volume of the silicon-based material layer to the total volume of the porous carbon matrix pores, the average pore size of the porous carbon matrix pores, and the thickness of the silicon-based material layer.

[0205] The preparation method of the secondary battery of Comparative Example 1 is similar to that of the secondary battery of Example 1, the main difference being that C2H4 is not introduced during the preparation of the silicon-based material layer, that is, the silicon-based material layer is a Si layer.

[0206] Table 1

[0207]

[0208] Test Case

[0209] Test method:

[0210] (1) Anode full charge rebound:

[0211] The original thickness of the negative electrode sheet is measured and recorded as W0. Then the assembled battery is disassembled after being fully charged, and the thickness of the negative electrode sheet after being fully charged is measured and recorded as W1.

[0212] Anode full charge rebound α=(W1-W0) / W0.

[0213] (2) Fast charging performance:

[0214] At 25°C, take the battery with pre-embedded copper wire and charge it to 4.25V at 0.33C constant current, and continue to charge it at constant voltage until the current is 0.05C. At this time, the battery is fully charged. Record the charging capacity at this time, which is the charging capacity of the first cycle; after the battery is left to stand for 30 minutes, discharge it to 2.5V at 0.33C constant current. This is a cyclic charging and discharging process. Record the discharge capacity at this time, which is the discharge capacity of the first cycle. Then start lithium plating, connect the copper wire to the positive electrode with the charging device, charge it at a constant current of 20uA for 2h, then connect the copper wire to the negative electrode with the charging device, charge it at a constant current of 20uA for 2h, and the copper wire after lithium plating is the reference electrode. The reference electrode potential defaults to 0mV. After lithium plating, charge the battery at a constant current of 2C, record the potential difference between the negative electrode and the reference electrode, and when the potential difference reaches 0mV, record the ratio of the charged capacity to the charging capacity of the first cycle. This ratio represents the fast charging performance of the secondary battery.

[0215] (3) Cycle life:

[0216] At 25°C, take the prepared battery and charge it to 4.25V at 0.5C constant current, and continue to charge it at constant voltage until the current reaches 0.05C. At this time, the battery is fully charged. The charging capacity at this time is recorded, which is the charging capacity of the first cycle. After the battery is left to stand for 30 minutes, it is discharged to 2.5V at 1C constant current. This is a cyclic charge and discharge process. The discharge capacity at this time is recorded, which is the discharge capacity of the first cycle. The battery is subjected to cyclic charge and discharge tests according to the above method, and the discharge capacity after each cycle is recorded until the discharge capacity of the battery decays to 80% of the discharge capacity of the first cycle. The number of cycles at this time is used to characterize the cycle life of the secondary battery.

[0217] (4) Energy density:

[0218] The battery was placed at a constant temperature of 25°C for 2 hours, then charged to 4.25V at 0.33C at 2.5V~4.25V, then charged at a constant voltage at 4.25V to a current ≤0.05C, placed at rest for 10 minutes, and then discharged to 2.5V at 0.33C, and the capacity C0 of the battery was recorded. VED is the ratio of C0 to the volume of the battery shell, which is the volume energy density (VED) of the secondary battery.

[0219] The test results are shown in Table 2 below:

[0220] Table 2

[0221]

[0222] It can be seen that the present application, by arranging sub-nano silicon clusters and sub-nano silicon carbide clusters in the silicon-based material layer, can make the prepared material less expansive, have better cycle performance and fast charging performance, and also have a higher energy density.

[0223] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.

[0224] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A silicon-carbon composite material, characterized in that: It includes a porous carbon matrix and a silicon-based material layer located in the pores of the porous carbon matrix, the silicon-based material layer includes sub-nano silicon clusters and sub-nano silicon carbide clusters, the surfaces of the sub-nano silicon carbide clusters are in contact with the surfaces of the sub-nano silicon clusters, and the silicon-based material layer is prepared by co-deposition of silicon source gas and carbon source gas.

2. The silicon-carbon composite material according to claim 1, characterized in that: The radial size of the sub-nanometer silicon cluster is 0.2nm~1nm; and / or the radial size of the sub-nanometer silicon carbide cluster is 0.2nm~1nm.

3. The silicon-carbon composite material according to claim 1, characterized in that: The specific surface area of ​​the porous carbon matrix is ​​≥800m 2 / g.

4. The silicon-carbon composite material according to claim 3, characterized in that: The specific surface area of ​​the porous carbon matrix is ​​800 m 2 / g~2000m 2 / g.

5. The silicon-carbon composite material according to claim 4, characterized in that: The specific surface area of ​​the porous carbon matrix is ​​800 m 2 / g~1200m 2 / g.

6. The silicon-carbon composite material according to claim 1, characterized in that: The total volume of the silicon-based material layer is less than the total volume of the pores.

7. The silicon-carbon composite material according to claim 6, characterized in that: The total volume of the silicon-based material layer accounts for 10% to 60% of the total volume of the pores.

8. The silicon-carbon composite material according to claim 7, characterized in that: The total volume of the silicon-based material layer accounts for 10% to 30% of the total volume of the pores.

9. The silicon-carbon composite material according to claim 1, characterized in that: The thickness of the silicon-based material layer is less than the pore diameter.

10. The silicon-carbon composite material according to claim 9, characterized in that: The average pore diameter of the pores is 5nm~50nm.

11. The silicon-carbon composite material according to claim 9, characterized in that: The average thickness of the silicon-based material layer is 2nm-20nm.

12. The silicon-carbon composite material according to claim 1, characterized in that: The particle size Dv50 of the silicon-carbon composite material is 3 μm to 30 μm.

13. The silicon-carbon composite material according to claim 12, characterized in that: The particle size Dv50 of the silicon-carbon composite material is 10 μm to 20 μm.

14. The silicon-carbon composite material according to claim 1, characterized in that: The surface of the porous carbon matrix is ​​also coated with a coating layer; the coating layer includes a carbon coating layer.

15. The silicon-carbon composite material according to any one of claims 1 to 14, characterized in that: In the silicon-carbon composite material, the mass percentage of silicon element is 20% to 40%, and the mass percentage of carbon element is 60% to 80%.

16. The silicon-carbon composite material according to any one of claims 1 to 14, characterized in that: The silicon-carbon composite material includes one or two of the following features: (1) Tap density is 0.7g / cm 3 ~1.3g / cm 3 ; (2) Specific surface area is 0.8m 2 / g ~1.5m 2 / g.

17. A method for preparing a silicon-carbon composite material, characterized in that: The steps include: Depositing a silicon-based material layer in the pores of the porous carbon matrix, the silicon-based material layer comprising sub-nanometer silicon clusters and silicon carbide clusters, the surface of the silicon carbide clusters being in contact with the surface of the sub-nanometer silicon clusters, and the silicon-based material layer being prepared by co-deposition of a silicon source gas and a carbon source gas; Depositing a silicon-based material layer in the pores of a porous carbon matrix includes: The porous carbon substrate is placed in a reaction container, and a mixed gas of a silicon source gas and a carbon source gas is introduced to perform vapor deposition; In the mixed gas, the volume ratio of the silicon source gas to the carbon source gas is 10:(1-5); The flow rate of the mixed gas is 0.05L / min~0.2L / min; The deposition temperature is 400℃~600℃; The deposition time is 30min~2h.

18. The method for preparing the silicon-carbon composite material according to claim 17, characterized in that: The method of introducing a mixed gas of silicon source gas and carbon source gas for vapor deposition includes one or more of the following features: (1) The silicon source gas includes SiH4; (2) The carbon source gas includes C2H4.

19. The method for preparing the silicon-carbon composite material according to any one of claims 17 to 18, characterized in that: After depositing the silicon-based material layer, the method further includes preparing a coating layer on the surface of the porous carbon matrix.

20. The method for preparing the silicon-carbon composite material according to any one of claims 17 to 18, characterized in that: The preparation method of the porous carbon matrix includes a template method, an acid-base activation method or a pyrolysis method.

21. The method for preparing the silicon-carbon composite material according to any one of claims 17 to 18, characterized in that: The preparation method of the porous carbon substrate comprises: mixing a template, a carbon source and a solvent to prepare a carbon solution; The carbon solution is subjected to a first heat treatment and then dried to prepare an expanded carbon precursor; subjecting the expanded carbon precursor to a second heat treatment to prepare a carbonized intermediate; The template in the carbonized intermediate is removed to prepare the porous carbon matrix.

22. The method for preparing the silicon-carbon composite material according to claim 21, characterized in that: The method for preparing the porous carbon substrate has one or more of the following characteristics: (1) The mass ratio of the template to the carbon source is (1-10):1; (2) The temperature of the first heat treatment is 70℃~90℃ and the time is 6h~10h; (3) The drying temperature is 120℃~140℃ and the drying time is 1h~4h; (4) The second heat treatment includes: heating to 400°C~600°C at a heating rate of 3°C / min~10°C / min and maintaining for 2h~6h.

23. A negative electrode plate, characterized in that: It comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises one or more of the silicon-carbon composite material according to any one of claims 1 to 16 and the silicon-carbon composite material prepared by the preparation method according to any one of claims 17 to 22.

24. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 23.

25. An electrical device, characterized in that: Includes one or more of the negative electrode sheet described in claim 23 and the secondary battery described in claim 24.

Citation Information

Patent Citations

  • Silicon carbide-coated hollow silicon material, preparation method thereof, and electrode and electrochemical device using silicon carbide-coated hollow silicon material

    CN112242504A

  • Silicon-carbon composite material as well as preparation method and application thereof

    CN114520313A